Cements of Yesterday and Today: Concrete of Tomorrow (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Concrete, a widely used construction material, has evolved significantly over time. This article explores the historical development of cements, highlighting the transition from traditional cements to modern alternatives. The article discusses the limitations of conventional cement, the emergence of innovative cementitious materials, and their potential to shape the concrete of tomorrow. By examining the advancements in sustainable and high-performance cements, this article sheds light on the future of concrete construction.